Particularitățile răspunderii subsidiare a membrilor organelor de conducere a debitorului insolvabil pentru fapta de ținere a contabilității fictive sau contrare legii [Articol] - Iosip, Andrei (Artpoligraf, 2020)
he application of the institution of the subsidiary liability to the members of the managing bodies of the insolvent debtor increased at the same time when the Moldovan Parliament adopted a new insolvency law on 29 June 2012. The analysis of this institution represents a practical interest, trying to identify the conditions of applicability, the elements of probation, the trial procedure and the juridical nature and the extent of the damage. Through this article, I have tried to specify the special conditions for employing the subsidiary liability for keeping fictitious or against the law accountancy. In practice, the application of this institution is complex and involves a very rigorous analysis of those circumstances which are necessary for applying the subsidiary liability to the responsible persons which have caused or aggravated the insolvency of the legal person.
PECULIARITIES OF THE SUBSIDIARY LIABILITY A MEMBER OF THE MANAGEMENT BODIES AN INSOLVABLE DEBT FOR THE FACT OF HOLDING A FICTIVE OR AGREEMENT ACCOUNTING
Keywords: insolvency law; subsidiary liability; debitorul insolvabil